2020
DOI: 10.3390/ijms21218158
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Polyethylene Glycol-Coated Gold Nanoparticle Toxicity and Inflammation In Vivo Using NF-κB Reporter Mice

Abstract: Polyethylene glycol (PEG) coating of gold nanoparticles (AuNPs) improves AuNP distribution via blood circulation. The use of PEG-coated AuNPs was shown to result in acute injuries to the liver, kidney, and spleen, but long-term toxicity has not been well studied. In this study, we investigated reporter induction for up to 90 days in NF-κB transgenic reporter mice following intravenous injection of PEG-coated AuNPs. The results of different doses (1 and 4 μg AuNPs per gram of body weight), particle sizes (13 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Short and long-term treatment with DOX was associated with higher levels of hepatic ROS, TNFα, and IL-6, over-activation of NF-κB, and reduced activities and expression of Nrf2 [ 3 , 4 , 6 , 8 , 30 , 31 , 32 ]. In addition, short-term treatment with AuNPs promotes hepatic and renal oxidative stress and inflammation by generating ROS and inflammatory cytokines, scavenging GSH, consuming SOD and CAT, and activating NF-κB [ 15 , 16 , 18 , 19 , 21 ]. Of note, the effect of AuNPs on hepatic and systemic Nrf2 signaling is not yet established in humans or animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short and long-term treatment with DOX was associated with higher levels of hepatic ROS, TNFα, and IL-6, over-activation of NF-κB, and reduced activities and expression of Nrf2 [ 3 , 4 , 6 , 8 , 30 , 31 , 32 ]. In addition, short-term treatment with AuNPs promotes hepatic and renal oxidative stress and inflammation by generating ROS and inflammatory cytokines, scavenging GSH, consuming SOD and CAT, and activating NF-κB [ 15 , 16 , 18 , 19 , 21 ]. Of note, the effect of AuNPs on hepatic and systemic Nrf2 signaling is not yet established in humans or animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the safety of these NPs is still uncertain. At the experimental levels, we and others have previously shown that short-term (7 days) exposure to small-sized gold NPs has resulted in a high rate of accumulation in the liver, and this was associated with high levels of ROS, lipid peroxidation, oxidative stress, activation of NF-κB, upregulation of inflammatory cytokines, and liver damage [ 15 , 16 , 17 , 18 , 19 , 20 ]. However, the effect of long-term exposure to AuNPs, as well as their combined effect with another risk factor on the liver structure and function is not well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is known that the toxicity of AuNP can be significantly reduced through surface modification. In general, PEG is widely used to reduce the toxicity of AuNPs [ 22 , 68 ]. Patlolla et al showed that the PEG coating of AuNPs reduced the ROS generation and hepatotoxicity compared to uncoated AuNPs [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…As AuNPs are known to be potentially toxic, several studies have been conducted to overcome this issue through surface modification. Various biological materials, including DNA [ 20 ], polyethylene glycol (PEG) [ 21 , 22 ], polyamidoamine [ 23 ], cell-penetrating peptides, and chitosan [ 24 , 25 ] have been used to enhance the biocompatibility of AuNPs. Furthermore, nucleic acid components can also be used to enhance drug loading.…”
Section: Introductionmentioning
confidence: 99%
“…Liver toxicity is a pivotal concern for risk assessment of environmentally exposed MNPs, as the liver is the major organ where MNPs are deposited and metabolized. In healthy adult rodents, MNP exposure caused hepatic inflammation, oxidative stress, DNA damage, and hepatocyte apoptosis and/or necrosis [ 34 , 35 , 36 ]. The above adverse outcomes in response to MNP exposure may be further aggravated in rodent models of NAFLD [ 13 ], suggesting the susceptibility of NAFLD individuals to MNPs.…”
Section: Discussionmentioning
confidence: 99%